Pengaruh Pemberian Poster Dan SMS Reminder Terhadap Kepatuhan Minum Tablet Besi Dan Kenaikan Kadar Hb Ibu Hamil Di Wilayah Kerja Puskesmas Sukoharjo - Alvionita, Indah, Sulastri, S.Kp., M.Kes (2017)
Introduction: The poster is a media health promotion using pictures and short messages with the aim of increasing awareness of health and can affect behavior. Control services to patients at home today many use SMS because it proved effective to improve adherence to therapy treatment someone who lived so as to improve health status. Purpose: to determine whether there is influence of giving posters and SMS Reminder adherence to iron tablets and increase hemoglobin levels of pregnant women. Methods: Quasi-experimental using pretest and post-test group design with a control group without randomization. This research was conducted in Puskesmas Sukoharjo in February 2017 with a sample of each of the 17 pregnant women in the treatment group and the control group. Purposive sampling technique used is a sheet denganInstrumen checklist and Hb measurement tools Easy Touch. Test to determine the data analysis using different test Non-parametric Mann Whitney. Results: pregnant .ibu adherent after the intervention there was 65% in the treatment group and 35% in the control group. Hb rate of pregnant women after the intervention has increased in the treatment group of 88% of mild anemia to normal as much as 59% and 41% still mild anemia Conclusions: shows the differences in adherence and hemoglobin concentration in which the treatment group experienced improvements in adherence and hemoglobin concentration compared with the control group with significance of 0.083 or p <0.05 in 0,002 or adherence and significance of p <0.05 in Hb.